The Baku Commune, 1917-1918 : class and nationality in the Russian Revolution - Suny, Ronald Grigor (Princeton, N.J. : Princeton University Press, 1972)
Roger Suny examines the Revolution in Baku, important provincial capital and oil center of the Russian empire. His study of Baku's national and class conflicts, Bolshevism as it developed in the city, and the failure of the Commune in 1918 amends our picture of the Revolution as the work ofa highly conspiratorial party, seizing power by force and imposing its will on a reluctant population by terror. Originally published in 1972. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Frontmatter -- Preface -- Acknowledgments -- Glossary of Terms and Abbreviations -- A Note on Transliteration and Dating -- Contents -- 1. Nationality and Class in Baku -- 2. Social Democracy and the Labor Movement in Baku 1898-1917 -- 3. The New Order and the Old Parties -- 4. From Economics to Politics: the Revolution Moves Left -- 5. October in Baku -- 6. From Politics to Armed Insurrection -- 7. The "Baku October": The "March Days" -- 8. Socialism by Decree -- 9. The Struggle for Baku -- 10. The Fall of the Commune -- 11. The Dictatorship of Tsentrokaspii: Right Socialists in Power -- 12. Conclusion -- Appendix: The Marxist Image of the Commune -- Bibliography -- Maps -- Index -- STUDIES OF THE RUSSIAN INSTITUTE
Includes bibliographical references.
English.
Online resource; title from digital title page (viewed on June 21, 2021).
JSTOR
Keywords: Baku (Azerbaijan) -- History; HISTORY -- Europe -- Eastern; HISTORY -- Europe -- Former Soviet Republics; HISTORY -- Europe -- Russia & the Former Soviet Union; HISTORY -- Europe -- General; Azerbaijan -- Baku; History